2009
DOI: 10.1021/la803308j
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Controlled Assembly of High Ordered/Disordered Dodecylamine Layers on HOPG: Consequences for DNA Patterning

Abstract: It is shown that temperature-controlled ordered layers of dodecylamine, self-assembled on highly oriented pyrolytic graphite (HOPG), are an appropriate substrate for aligning individual DNA molecules. High resolution atomic force microscopy (AFM) permits visualization of the lamellar structure of dodecylamine on HOPG. The DNA adsorbed on ordered dodecylamine layers is stretched and oriented along the lamellae, while DNA on disordered dodecylamine layers is found to be in a random conformation. Small DNA bubble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 34 publications
2
39
0
1
Order By: Relevance
“…The AFM results of this study indicated that circular DNA tends to form hexagonal patterns on bare HOPG surfaces. It should be pointed out that the DNA patterns obtained in this study are similar to those formed on the alkylamines modified HOPG (Severin et al , ; Adamcik et al , ; Dubrovin et al , ). However, the interactions of DNA and bare HOPG surface have not been well addressed in these studies.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The AFM results of this study indicated that circular DNA tends to form hexagonal patterns on bare HOPG surfaces. It should be pointed out that the DNA patterns obtained in this study are similar to those formed on the alkylamines modified HOPG (Severin et al , ; Adamcik et al , ; Dubrovin et al , ). However, the interactions of DNA and bare HOPG surface have not been well addressed in these studies.…”
Section: Resultssupporting
confidence: 83%
“…Therefore, direct adsorption of DNA onto HOPG surfaces seemed impossible from this point of view. An immobilization method have been developed in the recent studies, in which DNA molecules can be immobilized on alkylamines‐modified HOPG surfaces (Severin et al , ; Adamcik et al , , ; Klinov et al , ; Dubrovin et al , ). In the meantime, Oliveira‐Brett and Lin have demonstrated that DNA molecules can be freely adsorbed on HOPG surface (Brett and Chiorcea, ; Jiang and Lin, ; Chiorcea‐Paquim et al , ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a simplified procedure for modifying HOPG was proposed [30]. The authors used a graphite modifier composed of a hydrocarbon–peptide pair terminating with an amine group: (CH 2 ) n -(NCRH 2 CO) m -NH 2 [30,75,76]. The application of this graphite modifier to the hydrophobic HOPG surface results in the formation of a thin (0.7 nm) monolayer of positively charged polymer on the graphite surface, which promotes DNA binding.…”
Section: Experimental Designmentioning
confidence: 99%
“…For better observation of λ-DNA molecules and its stable arrangement on the HOPG substrate, here we used an amphilphilic dodecylamine (DA) layer which has two functional groups at its both ends; an alkyl chain for graphite and an amine group for DNA affinity. 13 A set of data illustrating the release of λ-DNA molecule from the DA-HOPG was recorded in Fig. 4.…”
Section: Resultsmentioning
confidence: 99%